Conversion of waste transformer oil into grease - N. Suhaila, A. Japar; Mohd Aizudin, Abd Aziz; Nurul Waheeda, Abdu Rahman (Springer Singapore, 2020)
This work is aimed to study the viability of waste transformer oil (WTO) as grease’s base oil. The shift of lubricant formulation towards high-performance materials and green formulation has led to the development of various lubricant formulations, including grease. Waste reduction is one of the formulation research trends where waste-based material, i.e. waste oil generated from automotive industries, is used as one of the grease constituents, and the grease’s characteristics and performances are evaluated and compared to the conventional grease. Variability of waste oil composition, a mixture of conventional and synthetic oil, has led to inconsistent grease properties and performances. This issue, however, is uncommon in power industry-generated waste oil and becomes a potential alternative to replace the waste oil from automotive industries, thus creating this opportunity. It was found that, after conducting WTO analysis, incorporating WTO in grease formulation and evaluating the WTO-based grease characteristic, the WTO is viable to be used as grease base oil.